KEBERAGAMAN DEWAN DIREKSI DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN KEBERLANJUTAN PERUSAHAAN MANUFAKTUR - Virginia Victoria Auparay; Muhammad Nabiil Lintang; Farah Margaretha Leon (RISTANSI: Riset Akuntansi, 2025)
This research focuses on analyzing the influence of diversity within the board of directors on the financial performance of manufacturing enterprises registered on the Indonesia Stock Exchange. Employing a purposive sampling approach, the study selected 16 companies that fulfilled predefined criteria during the 2019-2023 period, which yielded 80 observational data. Panel data regression served as the primary analytical method. The findings revealed that gender diversity, company size, and leverage substantially influence financial performance, whereas age diversity and experience diversity do not show a meaningful effect. These findings highlight the importance of considering aspects of gender diversity and capital structure in a company's financial strategy. In conclusion, board gender diversity and efficient debt management can improve financial performance, whereas the age and experience of board members do not directly affect performance.